Vegetarian Menu Substitution Practices and Nutrition Professionals' Involvement in the Foodservice Operations of Urban Kansas Childcare Centers - Jindrich, Caitlin; Sauer, Kevin; Daniels, Elizabeth; Procter, Sandra B.; Hanson, Jennifer Ann (My University, 2022)
Methods: An online questionnaire was sent to 155 urban Kansas childcare centers participating in the Child and Adult Care Food Program (CACFP). Initial survey distribution occurred on March 7, 2020, and responses were collected through August 2020. Results: Representatives from (N=85) childcare centers answered the survey, resulting in a response rate of 54.8%. When asked how frequently a vegetarian alternative was offered in lieu of the standard meal, 32.9% (n=28) answered “1-2 times/week”, 3.5% (n=3) answered “three times/week”, 15.3% (n=13) answered “four-five times/week”, and 41.2% (n=35) indicated they “never provide a vegetarian alternative”. Multiple centers reported routinely serving a vegetarian meal as the main meal center wide. One in four respondents (n=21) was unsure if vegetarian meals could qualify for CACFP reimbursement. When asked to indicate the credentials of the individuals involved in their centers’ menu process and/or foodservice operations, the most frequently cited credentials were the CACFP Child Nutrition Professional (CCNP), the CACFP Management Professional (CMP), and the School Nutrition Specialist (SNS) credentials which accounted for (n=11), (n=7), and (n=5) responses respectively. Over a third of the centers (36.4%, n=31) reported that their menus were written by the owner or an operations team member, and only 5.9% (n=5) reported menus being written by a dietitian/nutritionist. Application To Child Nutrition Professionals: The majority of the centers provided a vegetarian alternative at least once a week. However, the lack of confidence surrounding CACFP reimbursement for vegetarian meals highlights an important knowledge gap. In addition, many of the centers’ menus were written by the owner or an operations team member suggesting an underutilization of the expertise nutrition professionals have to offer.
Keywords: Childcare; Child Nutrition; Feeding Practices; Vegetarian